2016
DOI: 10.1097/md.0000000000004614
|View full text |Cite
|
Sign up to set email alerts
|

Features of triple-negative breast cancer

Abstract: The aim of this study was to determine the features of triple-negative breast cancer (TNBC) using a large national database. TNBC is known to be an aggressive subtype, but national epidemiologic data are sparse. All patients with invasive breast cancer and known molecular subtype diagnosed in 2010 to 2011 were identified from the National Cancer Data Base (NCDB). Patients with and without TNBC were compared with respect to their sociodemographic and clinicopathologic features. TNBC was present in 38,628 of 295… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(75 citation statements)
references
References 21 publications
3
69
1
2
Order By: Relevance
“…6 Magdalena et al did a study by Analysing 38,813 cases from the national cancer database in United Kingdom and they found that the incidence of TNBC varied by region from 10.8% in New England to 15.8% in the east south central US. 10 Triple negative breast cancers in Asian population are found to be associated with younger age of onset, increasing tumour size, increased prevalence of axillary lymph nodal involvement, higher histological grade of tumor and poor prognosis though our study did not found any significant relationship when we compared the receptor status with grade, stage of disease and age groups. 11 This difference in results could be because of the increased prevalence of higher grade tumours and late diagnosis in our population leading to more cases without ER/PR positivity.…”
Section: Discussioncontrasting
confidence: 69%
“…6 Magdalena et al did a study by Analysing 38,813 cases from the national cancer database in United Kingdom and they found that the incidence of TNBC varied by region from 10.8% in New England to 15.8% in the east south central US. 10 Triple negative breast cancers in Asian population are found to be associated with younger age of onset, increasing tumour size, increased prevalence of axillary lymph nodal involvement, higher histological grade of tumor and poor prognosis though our study did not found any significant relationship when we compared the receptor status with grade, stage of disease and age groups. 11 This difference in results could be because of the increased prevalence of higher grade tumours and late diagnosis in our population leading to more cases without ER/PR positivity.…”
Section: Discussioncontrasting
confidence: 69%
“…The existence of high transcriptomic correlation between canine MGC subtypes (ductal and simple) and human TNBC might be more important since TNBC has been highlighted in clinical and biomedical research due to its aggressive characteristics with poor prognosis. It has been known that the most common histological subtype of TNBC is invasive ductal carcinoma and their genetic profiles are shared by basal-like BC [ 39 , 40 ]. Thus, our results suggested that transcriptome signature of canine MGC and subtypes is able to represent the origin and characteristics of human BC.…”
Section: Discussionmentioning
confidence: 99%
“…8 Basically, breast cancer treatment constitutes surgery, chemotherapy, and radiotherapy. 9 There is an urgent need for chemotherapeutics that act selectively to inhibit neoplastic cell growth, leaving the non-tumor cells intact. 10 However, the majority of the drugs used in chemotherapy are mutagenic and cause damage to DNA from the tumor and non-tumor cells, leading to the death of rapidly dividing cells, which is associated with the collateral effects observed in patients.…”
Section: Introductionmentioning
confidence: 99%